Electron-deficient pyridinium salts/thiourea cooperative catalyzed O-glycosylation via activation of O-glycosyl trichloroacetimidate donors - Shaw, Mukta; Kumar, Yogesh; Thakur, Rima; Kumar, Amit (Beilstein Journal of Organic Chemistry, 2017)
The glycosylation of O-glycosyl trichloroacetimidate donors using a synergistic catalytic system of electron-deficient pyridinium salts/aryl thiourea derivatives at room temperature is demonstrated. The acidity of the adduct formed by the 1,2-addition of alcohol to the electron-deficient pyridinium salt is increased in the presence of an aryl thiourea derivative as an hydrogen-bonding cocatalyst. This transformation occurs under mild reaction conditions with a wide range of O-glycosyl trichloroacetimidate donors and glycosyl acceptors to afford the corresponding O-glycosides in moderate to good yields with predictable selectivity. In addition, the optimized method is also utilized for the regioselective O-glycosylation by using a partially protected acceptor.
Keywords: cooperative catalysis; electron-deficient pyridinium salts; O-glycoside; regioselectivity; thiourea

(untitled) - Peng, P.; Schmidt, R. R. (Acc. Chem. Res., 2017)

(untitled) - Zhu, X.; Schmidt, R. R. (Angew. Chem., Int. Ed., 2009)

(untitled) - Varki, A. (Glycobiology, 1993)

(untitled) - Doores, K. J.; Gamblin, D. P.; Davis, B. G. (Chem. – Eur. J., 2006)

(untitled) - Park, Y.; Harper, K. C.; Kuhl, N.; Kwan, E. E.; Liu, R. Y.; Jacobsen, E. N. (Science, 2017)

(untitled) - Seeberger, P. H. (Acc. Chem. Res., 2015)

(untitled) - Nigudkar, S. S.; Demchenko, A. V. (Chem. Sci., 2015)

(untitled) - Shaw, M.; Kumar, A.; Thakur, R. (Trends Carbohydr. Res., 2017)

(untitled) - Toshima, K.; Tatsuta, K. (Chem. Rev., 1993)

(untitled) - Davis, B. G. (J. Chem. Soc., Perkin Trans. 1, 2000)

(untitled) - Crout, D. H. G.; Vic, G. (Curr. Opin. Chem. Biol., 1998)

(untitled) - Withers, S. G. (Carbohydr. Polym., 2001)

(untitled) - Lopez, X.; Mujika, J. I.; Blackburn, G. M.; Karplus, M. (J. Phys. Chem. A, 2003)

(untitled) - MacMillan, D. W. C. (Nature, 2008)

(untitled) - Gröger, H.; Wilken, J. (Angew. Chem., Int. Ed., 2001)

(untitled) - Balmond, E. I.; Galan, M. C.; McGarrigle, E. M. (Synlett, 2013)

(untitled) - Vedachalam, S.; Tan, S. M.; Teo, H. P.; Cai, S.; Liu, X.-W. (Org. Lett., 2012)

Asymmetric Organocatalysis: from Biomimetic Concepts to Applications in Asymmetric Synthesis - Berkessel, A.; Groeger, H. (Wiley-VCH, 2005)
ISBN: 978-3-527-30517-9.

(untitled) - Chauhan, P.; Mahajan, S.; Kaya, U.; Hack, D.; Enders, D. (Adv. Synth. Catal., 2015)

(untitled) - Tu, Y.; Wang, Z.-X.; Shi, Y. (J. Am. Chem. Soc., 1996)

(untitled) - Sigman, M. S.; Jacobsen, E. N. (J. Am. Chem. Soc., 1998)

(untitled) - Corey, E. J.; Grogan, M. J. (Org. Lett., 1999)

(untitled) - Raup, D. E. A.; Cardinal-David, B.; Holte, D.; Scheidt, K. A. (Nat. Chem., 2010)

(untitled) - Weil, T.; Kotke, M.; Kleiner, C. M.; Schreiner, P. R. (Org. Lett., 2008)

(untitled) - Zhang, Z.; Schreiner, P. R. (Chem. Soc. Rev., 2009)

(untitled) - Zhang, Z.; Lippert, K. M.; Hausmann, H.; Kotke, M.; Schreiner, P. R. (J. Org. Chem., 2011)

(untitled) - Klausen, R. S.; Jacobsen, E. N. (Org. Lett., 2009)

(untitled) - Uraguchi, D.; Ueki, Y.; Ooi, T. (Science, 2009)

(untitled) - Hong, L.; Sun, W.; Yang, D.; Li, G.; Wang, R. (Chem. Rev., 2016)

(untitled) - Geng, Y.; Kumar, A.; Faidallah, H. M.; Albar, H. A.; Mhkalid, I. A.; Schmidt, R. R. (Angew. Chem., Int. Ed., 2013)

(untitled) - Palo-Nieto, C.; Sau, A.; Williams, R.; Galan, M. C. (J. Org. Chem., 2017)

(untitled) - Schmidt, R. R. (Angew. Chem., Int. Ed. Engl., 1986)

(untitled) - Kimura, T.; Eto, T.; Takahashi, D.; Toshima, K. (Org. Lett., 2016)

(untitled) - Mensah, E. A.; Azzarelli, J. M.; Nguyen, H. M. (J. Org. Chem., 2009)

(untitled) - Roy, R.; Palanivel, A. K.; Mallick, A.; Vankar, Y. D. (Eur. J. Org. Chem., 2015)

(untitled) - Kumar, A.; Kumar, V.; Dere, R. T.; Schmidt, R. R. (Org. Lett., 2011)

(untitled) - Portenkirchner, E.; Enengl, C.; Enengl, S.; Hinterberger, G.; Schlager, S.; Apaydin, D.; Neugebauer, H.; Knör, G.; Sariciftci, N. S. (ChemElectroChem, 2014)

(untitled) - Das, S.; Pekel, D.; Neudörfl, J.-M.; Berkessel, A. (Angew. Chem., Int. Ed., 2015)

(untitled) - Schmidt, R. R.; Michel, J. (Angew. Chem., Int. Ed. Engl., 1980)

(untitled) - Schmidt, R. R.; Kinzy, W. (Adv. Carbohydr. Chem. Biochem., 1994)

(untitled) - Schmidt, R. R.; Toepfer, A. (Tetrahedron Lett., 1991)

(untitled) - Fan, E.; Van Arman, S. A.; Kincaid, S.; Hamilton, A. D. (J. Am. Chem. Soc., 1993)

(untitled) - Albert, J. S.; Hamilton, A. D. (Tetrahedron Lett., 1993)

(untitled) - Raposo, C.; Crego, M.; Mussons, M. L.; Caballero, M. C.; Morán, J. R. (Tetrahedron Lett., 1994)

(untitled) - Cancogni, D.; Lay, L. (Synlett, 2014)

(untitled) - Michigami, K.; Terauchi, M.; Hayashi, M. (Synthesis, 2013)

(untitled) - Peng, P.; Schmidt, R. R. (J. Am. Chem. Soc., 2015)